Physical activity of children and adolescents with disabilities in Poland - First Para Report Card - Urbański, Piotr Kazimierz (Elsevier, 2025)
Background: This study provides a comprehensive evaluation of the Polish Para Report Card, which assesses various aspects of physical activity (PA) and related indicators among Polish children and adolescents with disabilities. This area has been under-researched, especially in the Polish context. Methods: The research methodology included systematic literature searches from 2014 to 2022, utilizing databases such as PubMed, EBSCO, and Google Scholar. This was complemented by outreach to governmental institutions for additional reports and data. The search strategy was aligned with the Global Matrix methodology and aimed at evaluating ten distinct indicators: Overall PA, Organized Sport and PA, Active Play, Active Transportation, Sedentary Behavior, Family and Peers, School, Community and Environment, Government.
Results: Grades were assigned to three of ten indicators. The Overall PA, Sedentary Behavior, and Government indicators each received a D-grade.
Conclusions: The study reveals the need for an extensive system to monitor PA among Polish children and adolescents with disabilities, and the development of effective strategies to enhance PA in this group. Children with disabilities in Poland are under-researched in the area of PA compared to their their counterparts without disabilities.